2016
DOI: 10.1038/cddis.2016.339
|View full text |Cite
|
Sign up to set email alerts
|

Desferrioxamine reduces ultrahigh-molecular-weight polyethylene-induced osteolysis by restraining inflammatory osteoclastogenesis via heme oxygenase-1

Abstract: As wear particles-induced osteolysis still remains the leading cause of early implant loosening in endoprosthetic surgery, and promotion of osteoclastogenesis by wear particles has been confirmed to be responsible for osteolysis. Therapeutic agents targeting osteoclasts formation are considered for the treatment of wear particles-induced osteolysis. In the present study, we demonstrated for the first time that desferrioxamine (DFO), a powerful iron chelator, could significantly alleviate osteolysis in an ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Furthermore, iron chelators suppress oxidative stress by inhibiting the activity of NADPH oxidase and suppressed expression of its subunit p22 phox [40]. Additionally, DFO induces HO-1 expression by blocking of p38 signaling pathway [41]. The decreased IL6 by DFO was in agreement with Demetrios Vlahakos et al [42].…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, iron chelators suppress oxidative stress by inhibiting the activity of NADPH oxidase and suppressed expression of its subunit p22 phox [40]. Additionally, DFO induces HO-1 expression by blocking of p38 signaling pathway [41]. The decreased IL6 by DFO was in agreement with Demetrios Vlahakos et al [42].…”
Section: Discussionsupporting
confidence: 81%
“…TGF-beta accelerates the formation of fibrous wraps and separates inflamed tissue from normal tissue, to reduce the formation of inflammatory granulation tissue, 70 while the increase of HO-1 can effectively inhibit the excessive action of osteoclasts. [71][72][73] Macrophages of the M1 and M2 phenotypes are indispensable in osteogenesis. Therefore, some scholars suggested that the key factor in determining macrophage-induced osteogenic or osteoclastic effects is the macrophage switch pattern rather than the specific macrophage phenotype.…”
Section: Pro-inflammatory and Pro-regenerative Gene Expression And Elmentioning
confidence: 99%
“…The over-activation of osteoclasts leads to an imbalance in bone resorption, which results in osteoclast-related diseases such as postmenopausal osteoporosis [15,16]. We therefore examined whether shikimic acid affected ovariectomy-induced osteoporosis in mice.…”
Section: Shikimic Acid Prevented Ovariectomy-induced Bone Loss In Micmentioning
confidence: 99%